READY TO NEW NORMAL ERA IN LAMONGAN REGENCY: LAMONGAN SIAP DALAM MENGHADAPI ERA NEW NORMAL - Iswatun Iswatun; Lailatul Fadliyah; Joko Susanto; Riris Medawati; Amellia Mardhika (Darmabakti Cendekia: Journal of Community Service and Engagements, 2023)
Background: Health education is important to handling Covid-19. During the pandemic, the government has recommended all citizens to apply health protocols, one of which is wearing a mask. Objective: The purpose of this activity is to provide education about prevention protocols using masks so that it can help government programs to suppress the rate of positive cases of Covid-19. Method: The method used is to provide education about the protocol for using masks correctly and distributing and distributing masks. Results: The result of the activity is that people become aware of wearing masks as a necessity for themselves and their families. Conclusion: Education is one of the public health efforts to prevent the spread of Covid-19. Through good education, it is hoped that the rate of spread of Covid-19 can be suppressed. Health promotion on how to prevent Covid-19 and providing information about the transmission method and severity of Covid-19 is continuously provided to the public to increase awareness